2012
DOI: 10.1124/dmd.112.049197
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Relative Gene Expression of UDP-Glucuronosyltransferases (2B7, 2B15, 2B17) in the Human Fetus

Abstract: UDP-glucuronosyltransferases (UGTs) catalyze phase II conjugation reactions and play an important role in the inactivation and elimination of several drugs. It is well known that the UGT activity in fetal livers is low compared with the UGT activity in adult livers. In this study the mRNA expression levels of the three human subfamilies, 2B7, 2B15, and 2B17, were determined in 20 adult and 60 fetal liver tissue specimens. The expression profile in fetal kidneys (N = 43), adrenals (N = 46), and lungs (N = 37) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
(35 reference statements)
2
18
0
Order By: Relevance
“…This assumption is in line with recent literature findings, where, compared with UGT1A1 and UGT1A9 that had almost no expression, a considerable amount of UGT2B15 mRNA was found in the human fetal liver and the expression level of UGT2B15 mRNA was positively correlated with fetal age. 35,36 These experimental data support the possibility of having an already relatively high expression of UGT2B15 in neonates, as compared with other UGT enzymes. Simulations showed that the UGT1A4 ontogeny profile (75% adult level at birth) sufficiently reflected UGT2B15 activity and was, hence, chosen as a surrogate in our model (Figure 3, table 1, and Supplementary Figure S1 online).…”
Section: Discussionsupporting
confidence: 66%
“…This assumption is in line with recent literature findings, where, compared with UGT1A1 and UGT1A9 that had almost no expression, a considerable amount of UGT2B15 mRNA was found in the human fetal liver and the expression level of UGT2B15 mRNA was positively correlated with fetal age. 35,36 These experimental data support the possibility of having an already relatively high expression of UGT2B15 in neonates, as compared with other UGT enzymes. Simulations showed that the UGT1A4 ontogeny profile (75% adult level at birth) sufficiently reflected UGT2B15 activity and was, hence, chosen as a surrogate in our model (Figure 3, table 1, and Supplementary Figure S1 online).…”
Section: Discussionsupporting
confidence: 66%
“…In this issue of Drug Metabolism and Disposition, the mRNA expression of UGT2B7, UGT2B15, and UGT2B17 in fetal tissues including fetal liver, lungs, adrenal glands, and kidneys is shown (Ekstrom et al, 2013). Although the mRNA levels were overall lower than those observed in adult human tissues, it is possible that the fetal UGT enzymes do contribute to detoxification of xenobiotics within the fetus.…”
Section: Knowledge On Enzyme-specific Changes During Pregnancymentioning
confidence: 87%
“…Besides the phase I enzymes discussed above, phase II enzymes such as uridine glucuronosyltransferase, sulfotransferase, glutathione S-transferase and peptidase activity have also been reported [36,37,38,39,40]. Somers et al [34] compared the catalytic activity of both phase I and II enzymes in isolated human lung parenchymal and hepatocyte cells using liquid chromatography-tandem mass spectrometry and found that some evidence for substantial sulfation and deesterification capacity in lung parenchymal cells.…”
Section: Transport and Metabolismmentioning
confidence: 99%